2018
DOI: 10.1097/md.0000000000011563
|View full text |Cite
|
Sign up to set email alerts
|

Desmoplastic melanoma versus spindle cell melanoma

Abstract: Desmoplastic melanoma (DM) and spindle cell melanoma (SCM) are 2 rare subtypes of melanoma. This study aims to investigate these 2 melanomas comprehensively by comparison.Cases were identified in the Surveillance, Epidemiology, and End Results (SEER) database (1973–2017).A total of 3657 DM and 4761 SCM cases were identified. DM's female-to-male ratio was 1:2 and SCM's was 0.62:1. The age distribution was similar. Both tumor mostly originated from skin and the eye and orbit was SCM-specific tumor site. Comparin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 25 publications
4
4
0
Order By: Relevance
“…5 ) and 2% were desmoplastic melanoma (Fig. 6 ), which are consistent with the rates of these subtypes of melanoma in other sites 38 41 .
Figure 5 ( A ) Clinical image of a 74-years-old man with an amelanotic papule in the scalp vertex; ( B ) Dermoscopic image of the lesion showing polymorphous vessels and ulceration.
…”
Section: Discussionsupporting
confidence: 86%
“…5 ) and 2% were desmoplastic melanoma (Fig. 6 ), which are consistent with the rates of these subtypes of melanoma in other sites 38 41 .
Figure 5 ( A ) Clinical image of a 74-years-old man with an amelanotic papule in the scalp vertex; ( B ) Dermoscopic image of the lesion showing polymorphous vessels and ulceration.
…”
Section: Discussionsupporting
confidence: 86%
“…5) and 2% were desmoplastic melanoma (Fig. 6), which are consistent with the rates of these subtypes of melanoma in other sites [38][39][40][41] .…”
Section: Discussionsupporting
confidence: 86%
“…It may also be a result of the efforts for early detection and the increase in total cases of melanoma [16]. The female-to-male ratio found in this study was approximately 1:2, as it was previously found by Xu et al [17]. Concerning the demographic characteristics, most of the patients with DM were white men over the age of 80, as is typically found in patients with CMM [18].…”
Section: Discussionsupporting
confidence: 78%